2020
DOI: 10.15294/jpii.v9i3.23358
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Learning Model through Video Documentary to Improve Environmental Knowledge of Coastal Residents of Palopo City, Indonesia

Abstract: This study aims to develop the Environmental Learning Model (ELM) by using documentary videos to improve knowledge of coastal residents of Palopo City about mangrove, wastewater, domestic waste, and liveable house. There were two phases used in this research. The first phase examined the concept of the lesson plan, guidedbook, video material, evaluation tests, and answer sheets that were validated by the experts. In the second phase, two reviewers examined the practicality and the effectivity of the learning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…It needs to drive the collaboration of many resources in supporting environmental education, including the curriculum, environment, and society (Asri et al, 2020;Sulaeman et al 2020). Alkaher and Gan (2020) suggested that schools have to engage their several stakeholders as school-state-community partnerships to cultivate the students' and community's environmental citizenship, school-business partnerships to improve the physical infrastructure, and assisted the promotion of education for sustainability in the school.…”
Section: Resultsmentioning
confidence: 99%
“…It needs to drive the collaboration of many resources in supporting environmental education, including the curriculum, environment, and society (Asri et al, 2020;Sulaeman et al 2020). Alkaher and Gan (2020) suggested that schools have to engage their several stakeholders as school-state-community partnerships to cultivate the students' and community's environmental citizenship, school-business partnerships to improve the physical infrastructure, and assisted the promotion of education for sustainability in the school.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the mangrove forest in Munte Village has changed its role to become a pond, and yet not regulated. The utilization of the coastal area must be controlled so that the damage and its impacts can be minimized as much as possible (Asri et al, 2020;Manik, 2018).…”
Section: Fishermen Group Learning Resultsmentioning
confidence: 99%
“…The results of observations of the implementation of learning show that not all learning stages are carried out well, even though professional development and training programs are necessary to increase academics' understanding and awareness of sustainability (Asri et al, 2020;Cebrián, 2018). Averagely, the assessment results of the learning components implementation are in the "Very Good" category.…”
Section: Learning Tool Validationmentioning
confidence: 99%
“…Based on the calculation, it is known that the validity coefficient was 0.77, which means the results of both assessments were valid. As for the reliability of the assessment was determined based on the percentage of agreement [68]. Based on the calculation, it is known that the reliability percentage of agreement was 95%, which means the results of both assessments were reliable.…”
Section: Environmental Awareness Campaignmentioning
confidence: 99%